Cost-effectiveness of palonosetron and dexamethasone-based triple and quadruple regimens in preventing highly emetogenic chemotherapy-induced nausea and vomiting. (3rd April 2022) - Halloush, Shiraz; Alhifany, Abdullah A.; Alkhatib, Nimer S.; Al Bawab, Abdel Qader; AL-Qawasmeh, Batool; Al Shawakri, Esra'a; Koeller, Jim
Abstract: Objective: Cost-effectiveness analyses that consider all currently used antiemetics in the case of emetogenic chemotherapy-induced nausea and vomiting (CINV) have not been performed yet. We aim to compare the cost-effectiveness of olanzapine (OLA), or/and neurokinin-1 receptor antagonists (NK-1-RAs), in combination with palonosetron (PAL) and dexamethasone (DEX) in preventing highly emetogenic CINV. Methods: Two decision analytic models were constructed. The first model was based on overall complete response (CR); the second model was based on rate of absence of nausea. Four antiemetic regimens PAL + DEX, NK-1-RAs + PAL + DEX, OLA + PAL + DEX, and PAL + NK-1-RA + DEX + OLA were compared in terms of cost, overall CR and rate of absence of nausea. Base case incremental cost-effectiveness ratio (ICER) estimates were calculated. The study was from the US payer perspective. Results: In terms of CR, the PAL + NK-1-RA + DEX + OLA was associated with the highest gains in the percentage of CR among all treatment regimens at base case ICERs of 4220 versus PAL + DEX, 4656 versus NK-1-RA + PAL + DEX, 16, 471 versus OLA + PAL + DEX. In term of rate of absence of nausea, the PAL + NK-1-RA + DEX + OLA was associated with the highest rate of absence of nausea among all the treatment regimens at base case ICERs of 2291 versus PAL + DEX, 1304 versus NK-1-RA + PAL + DEX, 2657 versus OLA + PAL + DEX. Conclusion: from an economic perspective, our study revealed that whether to use overall CR or/and rate of absence of nausea as determinants in the antiemetic decision for the CINV patients, the CR-based-, and rate of absence of nausea-based cost-effectiveness analyses, showed negotiable ICER estimates for the treatment PAL + NK-1-RA + DEX + OLA over the combinations PAL + DEX, NK-1-RA + PAL + DEX, and OLA + PAL + DEX regimens.